2017
DOI: 10.1021/acs.iecr.7b01223
|View full text |Cite
|
Sign up to set email alerts
|

Critical Assessment of Using an Ionic Liquid as Entrainer via Extractive Distillation

Abstract: Ionic liquids (ILs) have received much attention in the last two decades. One of the important applications is to use this relatively new class of compounds for the separation of azeotropic mixtures via extractive distillation. In this paper, overall extractive distillation processes of two azeotropic separation systems using a favorable ionic liquid as entrainer are rigorously developed. The optimized design flowsheets are compared with the conventional processes using an industrial entrainer. The two ionic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…The binary interaction parameters of the NRTL model for IL-TFP, IL-water, 30 and TFP-water 5 are listed in Supporting Information, Table S1. Meanwhile, the critical properties 32 and ideal gas heat capacity (CPIG) 33 are presented in the Supporting Information, Tables S2 and S3. With the parameters listed in Supporting Information, Tables S2 and S3, the vapor pressure and heat of vaporization can be calculated by Aspen Plus and the extractive distillation process can be simulated.…”
Section: Conceptual Designmentioning
confidence: 99%
“…The binary interaction parameters of the NRTL model for IL-TFP, IL-water, 30 and TFP-water 5 are listed in Supporting Information, Table S1. Meanwhile, the critical properties 32 and ideal gas heat capacity (CPIG) 33 are presented in the Supporting Information, Tables S2 and S3. With the parameters listed in Supporting Information, Tables S2 and S3, the vapor pressure and heat of vaporization can be calculated by Aspen Plus and the extractive distillation process can be simulated.…”
Section: Conceptual Designmentioning
confidence: 99%
“…[31,32] Thus, it highlights the need to systematically and quantitatively study the trade-off between process efficiency and cost by integrating solvent selection with process design intensification. ) has been identified as an efficient ionic liquid solvent for several azeotropic separation systems, ethanolwater, [33,34] acetone-methanol, [35] isopropyl alcohol dehydration. [36] In addition to significantly increasing the selectivity between the azeotropic pair, [EMIM][OAc] also has a relatively lower viscosity than other ionic liquid solvents.…”
Section: Case Studymentioning
confidence: 99%
“…The thermal stability of [EMIM][OAc] should also be considered for process design, which requires either to integrate the thermal degradation kinetics or to constrain the operating temperatures to a maximum value. Chen et al [35] reported that, by strictly operating below the ionic liquid degradation temperature, the degradation of [MMIM][DMP] for acetone/methanol extractive distillation was 16.8 kg/year with a loss cost of $2610 per year, which was much smaller than the equipment cost. Thus, in this work, we constrain the operating temperatures to be strictly below the [EMIM][OAc] degradation temperature (i.e., 433.15 K [37] ), to minimize the impact of thermal degradation.…”
Section: Case Studymentioning
confidence: 99%
“…The superscripts ‘pred’ and ‘corl’ represent the vaporization enthalpy of IL predicted by the Clausius–Clapeyron equation and the calculated value by the DHVLWT model, respectively. These methods of calculating thermodynamic properties are widely used and have obtained accurate results …”
Section: Simulation Of Extractive Distillation Processmentioning
confidence: 99%
“…These methods of calculating thermodynamic properties are widely used and have obtained accurate results. [38][39][40][41][42] Thermodynamic model for VLE data NRTL, a thermodynamic model proposed by Renon and Prausnitz, 43 is widely used in the correlation of the VLE data with ILs. [44][45][46][47] The equation for the NRTL model is as follows:…”
Section: Establishment Of Il Databasementioning
confidence: 99%